3-body energy terms in a quartet state of H3 - Brailsford, David F.; Ford, Brian (Elsevier, 1971)
Calculations of the 3-body energy term in a quartet (4A2 ) state of H3 (equilateral triangle nuclear-configurations) show a minimum in the 3-body energy for a side length of about 1.3 bohrs.